CXCR3+ T follicular helper cells induced by co-administration of RTS,S/AS01B and viral vectored vaccines are associated with reduced immunogenicity and efficacy against Malaria - Ewer (nee Russell), K; Bowyer, G; Grobbelaar, A; Rampling, T; Venkatraman, N; Morelle, D; Ballou, R; Hill, A (Frontiers Media, 2018)
Malaria remains a significant cause of morbidity and mortality in sub-Saharan Africa. An efficacious vaccine will be an essential part of attempts to eradicate the disease. A vaccine strategy targeting multiple stages lifecycle stages may be required to achieve a high level of efficacy. In a series of phase IIa clinical trials we tested different regimens of two vaccine platforms: RTS,S/AS01B, which induces antibody responses to target sporozoites and viral-vectored vaccines ChAd63-MVA ME-TRAP, which induce T cells that target infected hepatocytes. Concomitant administration of these vaccines significantly reduced humoral immunogenicity and protective efficacy against controlled human malaria infection. Strong Th1 cytokine responses induced by MVA ME-TRAP were associated with a skew in circulating T follicular helper cells towards a CXCR3+ phenotype and the observed reduction in antibody quantity and quality. This study illustrates that while a multistage-targeting vaccine strategy could provide high-level efficacy, the regimen design will require careful optimisation.